Anthropometric and Metabolic Responses in FTO rs9939609 Gene Polymorphism after a Multidisciplinary Lifestyle Intervention in Overweight and Obese Adolescents - Barbian, Cláudia Daniela; Reuter, Cézane Priscila; Renner, Jane Dagmar Pollo; da Silva, Priscila Tatiana; Klinger, Elisa Inês; Hobkirk, James Philip; de Moura Valim, Andréia Rosane; Burgos, Miria Suzana (Journal of Pediatric Genetics, 2020)
Few studies show the potential changing effect of fat-mass and obesity-associated (FTO) rs9939609 gene on cardiometabolic risk after a lifestyle intervention. This study aims to evaluate whether overweight and obese adolescents, carriers of the risk genotypes for obesity of the FTO rs9939609 gene polymorphism, have different anthropometric and biochemical responses to an interdisciplinary intervention program. The quasi-experimental study involved 34 adolescents aged 10 to 15 years. Schoolchildren with AA/AT genotype decreased glucose, total cholesterol, low-density lipoprotein cholesterol, and increased high-density lipoprotein cholesterol. However, there were no differences between the genotypes, suggesting that the “A” allele did not modify the subject's response to the intervention program.
Keywords: clinical trial; obesity; genetic polymorphism